The best vegetarian dishes I know - Jardine, Jeanne (Salt Lake City, UT : Project Gutenberg, 2023)
"The Best Vegetarian Dishes I Know" by Jeanne Jardine is a culinary guide focused on vegetarian cuisine, likely written in the early 20th century. This work presents a collection of recipes aimed at providing tasty and nourishing meals without the use of meat, specifically excluding fish. The book emphasizes that these dishes are suitable for "good plain" cooks and aims to dispel the notion that vegetarian cooking is necessarily more expensive than meat-based meals. The beginning of the book introduces the reader to the author's philosophy on vegetarianism and sets the context for the recipes to follow. Jardine outlines her intention to create accessible and elegant dishes that utilize a variety of ingredients including vegetables, eggs, and dairy. She also advises readers to understand each recipe fully before commencing cooking, highlighting that the same recipe can yield different results depending on the chef's techniques. Overall, the opening establishes a helpful and encouraging tone, preparing readers for the practical recipes and rich culinary experiences that are to come. (This is an automatically generated summary.)
Release date is 2023-02-28
The Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Vegetarian cooking; Cooking (Vegetables)